SERVICE MARKETING STRATEGIES APPLIED BY BYD AUTOMOBILE NANCHANG HONGYUN 4S STORE - Xiong, Ying (Journal of Buddhist Education and Research (JBER), 2023)
In recent years, as affected by the COVID-19, there has been a decline in China's automobile industry and BYD Automobile Nanchang Hongyun’s 4S Store branches as well. During the epidemic, the development of auto 4S Store branches has been even more difficult. Therefore, in order to improve the competitiveness of 4S Store branches, it is necessary for BYD Automobile Nanchang Hongyun to improve its original service marketing model, service capabilities, and market competitiveness in a targeted manner. This paper aimed to investigate the service marketing strategies of BYD Auto Nanchang Hongyun 4S store through an analysis of the 7Ps of the marketing mix, its marketing environment based on the PEST analysis. In addition, the five forces model analysis and the SWOT analysis were employed. The result revealed that the company emphasized three out of the 7Ps marketing mix elements: Segmenting, Targeting and Positioning. The research recommended that the company implement service marketing optimization for future development.